Effect of Natural Fiber Network on Permeability and Tensile Strength of Composites through Vacuum Infusion Process. Issue 2 (4th March 2017) - Subbiah, Rajkumar; Tjong, Jimi; Nayak, S. K.; Sain, M.
ABSTRACT: This investigation is primarily focused to study the effect of fiber network on the permeability in vacuum infusion molding process. The unsaturated permeability of several natural fiber mats with different networks is measured. The experimental permeabilities are fitted by the Kozeny model and contact angle model. The outcome highlighted that the contact angle model shows more precise results as compared to kozeny model. The obtained permeability for the random fiber mats shows higher values than directional fiber mat. Furthermore, the maximum increase in tensile strength is observed in the unidirectional composites and the flow along the fiber direction.